Canva Based Poster Media for Halamanku Theme in Elementary Social Studies: Media Poster Berbasis Canva untuk Tema Halamanku dalam Mata Pelajaran Sosial di Sekolah Dasar - Ayu Ida Fitria; Vanda Rezania (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Learning media play a crucial role in facilitating meaningful Social Studies instruction in elementary schools, particularly for themes requiring concrete visual representation. Specific Background: Poster media as static visual tools can present information concisely and attractively, yet classroom practice still relies heavily on lectures and textbooks, resulting in passive student participation. Knowledge Gap: The limited availability of engaging visual media for the “Halamanku” theme indicates a need for systematically designed digital posters aligned with curricular content. Aims: This study aims to develop a Canva based poster learning media for the “Halamanku” topic in elementary Social Studies using a research and development approach. Results: Employing the ADDIE model limited to Analysis, Design, and Development stages, the study produced a digital poster characterized by clear layout, child friendly visuals, relevant content, and aesthetic balance, meeting principles of good instructional media. Novelty: The research presents a structured development process of curriculum aligned poster media created entirely with an accessible online design platform. Implications: The resulting product can serve as an alternative visual teaching aid to support active, engaging, and meaningful Social Studies learning for elementary students without requiring advanced design expertise. Highlights: A structured three stage development process generated a curriculum aligned visual product. The digital design demonstrates clarity, readability, and child appropriate aesthetics. The product is suitable as a classroom visual aid for thematic instruction. Keywords: Poster Learning Media; Canva; Elementary Social Studies; Visual Instructional Media; ADDIE Model